2016
DOI: 10.1016/j.msea.2016.04.092
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure and mechanical properties of selectively laser melted AlSi10Mg: The effect of a conventional T6-like heat treatment

Abstract: The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. ABSTRACTSelective laser melting (SLM) of aluminium is of research interest because of its potential benefits to high value manufacturing applications in the aerospace and automotive industries. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
205
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 538 publications
(229 citation statements)
references
References 38 publications
18
205
2
4
Order By: Relevance
“…Similar anisotropy has been seen in previous work and ascribed to microstructural anisotropy stemming from the asymmetric heat flux during laser irradiation and cooling and from the preference for flaws to align in this direction [23]. The microstructures of the SLM manufactured AlSi10Mg alloy using the same materials and process as used in this study have been previously reported by Aboulkhair et al [24].…”
Section: Quasi-static Tensile Coupon Tests Of the Parent Materialssupporting
confidence: 86%
“…Similar anisotropy has been seen in previous work and ascribed to microstructural anisotropy stemming from the asymmetric heat flux during laser irradiation and cooling and from the preference for flaws to align in this direction [23]. The microstructures of the SLM manufactured AlSi10Mg alloy using the same materials and process as used in this study have been previously reported by Aboulkhair et al [24].…”
Section: Quasi-static Tensile Coupon Tests Of the Parent Materialssupporting
confidence: 86%
“…In addition, the stress and internal stresses that occur in the as‐built structure by rapid solidification are eliminated by SR heat treatment, which causes the material to soften. However, with the loss of MPBs as a result of T6 heat treatment, hardness is further reduced …”
Section: Resultsmentioning
confidence: 99%
“…[37,[111][112][113][114] Secondly, the scan speed has a noteworthy impact on the shape of the melt pool, with increasing scan speeds the melt pool width decreases, which requires to reduce hatch distances to account for it, while the melt pool length increases. References pure Al >99.5 [143] AlSi0.5 $100 [120] Al6061 (AlMg1SiCu) 96.5 [144] Al7075 (AlZn5.5MgCu) 95.1 [145] Al7075 þ 4 wt% Si 98.9 [145,146] A356 (AlSi7Mg0.3) 99.8 [147] A357 (AlSi7Mg0.6) 99.5 [148] A360 (AlSi9.5Mg0.5) 99.8 [146] AlSi10Mg 99.5 %100 [36,64,73,115,120,122,131,137,[149][150][151][152][153] AlSi25 %100 [120] AlMg3 %100 [120] AlSi9Cu3 99.5 [137] Al-3.5Cu-1.5Mg-1Si >98 [154] AlMgScZr (Scalmalloy) >99 %100 [100,116,137] AlSi10Mg reinforced with 5 wt% TiC 99.5 [155] AlSi10Mg reinforced with 1 wt% TiB 2 99.2 [152] AlSi10Mg reinforced with 10 wt% TiB 2 98 [152] AlSi10Mg reinforced with 0.5 wt% MgAl 2 O 4 99.3 [152] a) common relates to consistent results found in multiple publications. In addition to the complexity of determining a suitable set of fabrication parameters, various raw materials differ widely in their requirements and their absorptivity of the laser power, and their heat conductivity.…”
Section: Mechanical Propertiesmentioning
confidence: 99%